The phase shift between potential and kinetic energy in human walking - Cavagna, Giovanni A.; Legramandi, Mario A. (Journal of experimental biology, 2020)
It is known that mechanical work to sustain walking is reduced thanks to a transfer of gravitational potential energy into kinetic energy as in a pendulum. The factors affecting this transfer are unclear. In particular it is not known the phase relationship between potential and kinetic energy curves of the center of mass. This relationship has been measured in this study. The normalized time intervals: i) α, between maximum of kinetic energy in the sagittal plane Ek and minimum of gravitational potential energy Ep, and ii) β, between minimum of Ek and maximum of Ep, have been measured during walking at various speeds (0.5-2.5 m s−1). In our group of subjects, α=β at 1.6 m s−1, indicating that, at this speed, the time difference between Ep-Ek extremes is the same at the top and the bottom of the trajectory of the center of mass. It turns out that at the same speed: i) the work done to lift the center of mass equals the work to accelerate it forwards, ii) the Ep-Ek energy transfer approaches a maximum and iii) the mass specific external work per unit distance approaches a minimum.